A cibercultura e a expansão interdisciplinar da área da comunicação - Valencia, Maria Cristina Palhares (2013)
This investigation produced a panorama of cybercultural themes, as well as their theoretical and methodological fundamentals and analytical methods used in theses and dissertations in the field of Communication in Brazil, in the triennia of 1995 to 2010. Abstracts of researches conducted in Postgraduate Programs spanning over fifteen years of activity were analyzed, in view of the relevance indicated by the number of papers presented in the aforementioned period. The methodology adopted here was of a theoretical-empirical and qualitative-quantitative nature, underpinned by inquiries and records of texts pertinent to the theme and information available in library catalogs and in the institutional databases of theses of CAPES (Federal Agency for the Support and Improvement of Higher Education) and IBICT (Brazilian Institute of Science and Technology Information). The bibliographic data and analytical observations about the collected material were indexed in a database developed in Access software, and were used to generate charts in Microsoft Excel so as to represent the elements indicated by researchers of the area during the aforementioned period. The research problems, as well as the reasons that motivated the researchers in their investigations into cyberculture and the adoption of other theories and methodologies about the objects analyzed, for example, are mentioned in the course of this investigation and can be explained by the social, economic, political and cultural transformations resulting from the new information and communication technologies. Among other factors addressed in this research, changes in the lines of research in postgraduate programs in Communication were also identified, which indicate the redimensioning of the field of communication, opening a space for the formation of a subfield that of Cyberculture. Theoretical frameworks outlined, for example, by Virilio, Castells, Landow, Flusser, Levy, Johnson, Guiddens, Negri, Trivinho, Sataella, Manovich, and Bergson, reinforce this mutation and renewal, following the expansion of the field of Communication. The authors involved in these perspectives are, among others, Gastón Bachelard, Michel Foucault, Eugênio Trivinho, Erick Felinto and Francisco Rüdiger